Factors Affecting Permeability Reduction of MICP for Fractured Rock - Peng, Shuquan; Di, Hu; Fan, Ling; Fan, Wang; Qin, Liu (Frontiers in Earth Science, 2020)
Microbial induced calcite precipitation (MICP) has shown great potential to reduce the permeability of fractured rock, but its permeability reduction characteristic, affected by cementing solution concentration and geometric morphology of fractured rock, has not been presented. In this paper, a self-designed device for experimental MICP grouting and seepage performance was used to study the effects of factors including urea and calcium chloride concentration, fracture roughness and aperture on the permeability reduction of MICP on fractured rock. During the experiment, the same total volume of cement solution was injected into each sample with the same injection times. Based on the experimental results, the Darcy permeability coefficient of MICP grouted fractured rock was reduced to 3–5 × 10–5 m/s by four orders of magnitude smaller than that of non-grouted fractured rock. An increase in fracture roughness, urea and calcium chloride concentrations, as well as a decrease of fracture aperture, caused the MICP grouting ratio in fractured rocks to decrease, as well as a decrease of the Darcy permeability coefficient. In addition, the permeability reduction of MICP on fractured rock increased with the decrement of the above four factors. The permeability coefficient of grouted fractured rock and the permeability reduction of MICP were excessively sensitive to urea concentration. Furthermore, the permeability reduction was fitted well by power function. The research results could provide important guidance and reference significance for MICP grouting application in rock engineering.